Lakóingatlan-árak és települési különbségek - Békés Gábor; Horváth Áron; Sápi Zoltán (Hungarian Academy of Sciences, Institute of Economics, 2016)
– This paper analyses the factors affecting the price level of Hungarian residential real estate using individual sales data. We focus on the role of the location of the property. We show that geographical factors are relevant in explaining housing prices using traditional type groups constructed from mentioned factors. Our study makes two contributions. First, we find that every group of variables may be important in disentangling real estate prices; individual factors explain 2-5% of the variance of housing prices, while together they account for 15% of the variance. Second, our results imply that in estimating a hedonic model, in addition to agglomeration and income effects, geographical factors are essential to consider.
Keywords: R30; R31; 330; housing; hedonic pricing; geographic factors